Optimal Income Taxation under Monopolistic Competition - Alexander Tarasov; Robertas Zubrickas (Center for Economic Studies and ifo Institute (CESifo), 2021)
This paper is concerned with cross-dependencies between endogenous market structure and tax policy. We extend the Mirrlees (1971) model of income taxation with a monopolistic competition framework with general additively separable consumer preferences. We show that price and variety distortions resulting from the market structure imply that income tax policy needs to be complemented with commodity or firm taxation to achieve the constrained social optimum. We calibrate the model and find that, when choosing optimal tax policy, the failure to account for the market structure results in a welfare loss of 1:77 percent. Motivated by practical cases, we study a policy regime that is solely based on income taxation. Under this policy regime, departures from the social optimum can be compensated by lower and less regressive income taxes than those obtained under the regime with all forms of taxation. We also examine the role of consumer preferences for policy outcomes and show that it is substantially amplified by an endogenous market structure.
Keywords: D43; H21; L13; 330; tax policy; monopolistic competition; variety effect; consumer preferences; endogenous labor